2020
DOI: 10.1186/s40168-020-00827-8
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the mechanisms shaping the surface ocean microbiota

Abstract: Background: The ocean microbiota modulates global biogeochemical cycles and changes in its configuration may have large-scale consequences. Yet, the underlying ecological mechanisms structuring it are unclear. Here, we investigate how fundamental ecological mechanisms (selection, dispersal and ecological drift) shape the smallest members of the tropical and subtropical surface-ocean microbiota: prokaryotes and minute eukaryotes (picoeukaryotes). Furthermore, we investigate the agents exerting abiotic selection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
216
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(238 citation statements)
references
References 111 publications
(155 reference statements)
18
216
4
Order By: Relevance
“…Slight shifts in immune function were found to impact the respiratory microbial communities and they may have been at play here. The strong variation in intra-core zOTUs within individuals highlights that the lung microbiota of dolphins is dynamic and there are likely internal physiological as well as external factors such as temperature [48] involved that impact the bacterial communities on a day-to-day basis.…”
Section: Discussionmentioning
confidence: 99%
“…Slight shifts in immune function were found to impact the respiratory microbial communities and they may have been at play here. The strong variation in intra-core zOTUs within individuals highlights that the lung microbiota of dolphins is dynamic and there are likely internal physiological as well as external factors such as temperature [48] involved that impact the bacterial communities on a day-to-day basis.…”
Section: Discussionmentioning
confidence: 99%
“…recently(Liu et al, 2020;Logares et al, 2020;Stegen et al, 2013;Vass et al, 2020;Yan et al, 2017). For example, studies in lakes found that deterministic processes govern the structure of bacterial communities at different temporal scales (Kent, Yannarell, Rusak, F I G U R E 4 (a) Temporal changes in bacterial relative abundance in Gossenköllesee (GKS) and in Piburgersee (PIB).…”
mentioning
confidence: 99%
“…In the last few years, the study of community assembly in natural ecosystems has shifted its focus from a descriptive “who is there?” approach, to elucidating the relative contribution of stochastic vs. deterministic processes on community assembly (e.g. [97] , [98] , [99] ). Both approaches are indeed pertinent to increase our understanding of the particular ecosystem under investigation.…”
Section: Experimental Systemsmentioning
confidence: 99%
“…In addition to the more common β-diversity analyses, they used null model analysis, neutral models, and co-occurrence networks to assess the relative importance of community assembly processes in soils linked to measured abiotic environments and geographic patterns. Following similar goals and overall analytical framework, Logares and co-workers [99] assessed the drivers of prokaryotic and picoeukaryotic community structure in the sunlit ocean.…”
Section: Representative Studiesmentioning
confidence: 99%